A study of photostability and compatibility of the anti-chagas drug Benznidazole with pharmaceutics excipients. (January 2015) - Santos, Fabiana L. A.; Rolim, Larissa A.; Figueirêdo, Camila B. M.; Lyra, Magaly A. M.; Peixoto, Monize S.; Ferraz, Leslie R. M.; Soares-Sobrinho, José L.; Lima, Ádley Antonini Neves de; Lima Leite, Ana Cristina; Rolim Neto, Pedro José
Abstract Context: Benznidazole (BNZ) is an antiparasitic with trypanocidal properties for the etiological treatment of Chagas disease since 1973. Monitoring the stability of this drug is one of the most effective methods of assessment, forecasting and prevention of problems related to quality product. Objective: To investigate the direct and indirect photodegradation of BNZ and to evaluate the interference of the excipients used in the forms dosage solid as well as to shed light on the chemical structure of the degradation products obtained. Materials and methods: To perform this work we adopted the "ICH Harmonised Tripartite Guideline: Photostability Testing of New Drug Substances and Products Q1B" (Guideline Q1B). We used benzonidazole (BNZ) (N-benzil-2-(2-nitroimidazol-1-il) acetamide) (LAFEPE®, Recife, Brazil) and various excipients; beyond high-performance liquid chromatography (HPLC), differential scanning calorimetry (DSC), infrared spectroscopy (IR) and mass spectrometry/mass spectrometry (MS/MS). The indirect photodegradation of BNZ was carried out using physical mixtures with 13 pharmaceutical excipients commonly used in the preparation of solid dosage forms. Results: HPLC and MS/MS techniques were selected for the identification of two photoproducts (PPs) and photoreactions found in direct and indirect tests with the microcrystalline cellulose, considered a critical excipient. Discussion: Despite variations in the infrared spectrometry, differential scanning calorimetry and differential thermogravimetry curves, these techniques are not conclusive since the study of photodegradation of the drug caused decay of 30%, according to the ICH. Conclusions: The results show that BNZ only undergoes direct photodegradation, since no new PPs were found for a combination of the drug and excipients.